BPEL4WS 1.1. to WS-BPEL 2.0 a migration path. - Alves, Alexandre (SOA webservices journal.)
BPEL4WS V1.1 is a public draft release of the "Business Process Execution Language for Web Services" specification dated May 3, 2003. BPEL4WS V1.1 is arguably the de facto standard for Business Process Management (BPM); however, because it's a draft release, BPEL4WS V1.1 has several shortcomings that will be addressed by the next release of the specification (named WS-BPEL 2.0), which is targeted to be released either toward the end of this year or during the beginning of 2006.